2020
DOI: 10.1523/jneurosci.2155-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation-Based Connectivity Architecture Is Dominated by an Intrinsic Spatial Organization, Not Cognitive State or Frequency

Abstract: Functional connectivity of neural oscillations (oscillation-based FC) is thought to afford dynamic information exchange across task-relevant neural ensembles. Although oscillation-based FC is classically defined relative to a prestimulus baseline, giving rise to rapid, context-dependent changes in individual connections, studies of distributed spatial patterns show that oscillation-based FC is omnipresent, occurring even in the absence of explicit cognitive demands. Thus, the issue of whether oscillation-based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 81 publications
(104 reference statements)
7
19
0
Order By: Relevance
“…An EEG study in source-space showed that phase-coupling is spatially consistent when calculated over several minutes of different tasks (resting state, video viewing, and flashing gratings) with similar modular organization across frequency bands (Nentwich et al, 2020). Finally, a recent ECoG study contrasted various cognitive states including rest and short (1.5-2.5 s) pre-stimulus and post-stimulus epochs of different tasks (Mostame and Sadaghiani, 2021). Phase-and amplitude-coupling revealed a highly similar, largely state-invariant spatial component across cognitive states.…”
Section: Stability Of the Intrinsic Electrophysiological Connectome Across Cognitive Statesmentioning
confidence: 93%
“…An EEG study in source-space showed that phase-coupling is spatially consistent when calculated over several minutes of different tasks (resting state, video viewing, and flashing gratings) with similar modular organization across frequency bands (Nentwich et al, 2020). Finally, a recent ECoG study contrasted various cognitive states including rest and short (1.5-2.5 s) pre-stimulus and post-stimulus epochs of different tasks (Mostame and Sadaghiani, 2021). Phase-and amplitude-coupling revealed a highly similar, largely state-invariant spatial component across cognitive states.…”
Section: Stability Of the Intrinsic Electrophysiological Connectome Across Cognitive Statesmentioning
confidence: 93%
“…During rest, brain activity in sub-second time-scales is dominated by alpha oscillations [6], but involves frequency-specific inter-areal correlation structures throughout the 1-100 Hz range [9][10][11][12][13][14]. Importantly, the intrinsic spatial organization of spontaneous restingstate FCs observed both with MEG and functional magnetic resonance imaging (fMRI) is predictive of individual variability in task performance [12,[14][15][16], suggesting that such resting-state FC networks reflect underlying individual brain structural organization [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that modulations in oscillation dynamics would be obtained via inter-individual differences in the neuromodulation levels, which could result in differences in systems-level net E/I balance (or neural gain). In the brain criticality framework, the carriers of different variants of the COMT Val 158 Alternatively, COMT and especially BDNF could induce plastic changes in the structural connectivity networks (SC) [50,51] which in turn could lead to changes in FC [17]. To test these hypotheses, we measured resting-state brain dynamics with MEG and estimated local oscillation amplitudes, large-scale phase synchronization, and LRTCs from individually source-reconstructed MEG data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations